2017
DOI: 10.1021/acs.jpclett.7b01220
|View full text |Cite
|
Sign up to set email alerts
|

Raman Radial Mode Revealed from Curved Graphene

Abstract: One of the unsolved fundamental issues of graphene is establishing an appropriate way to discern layers of graphene structures. We report a simple methodology to analyze graphene structures using Raman signals in the range of ∼100 to ∼500 cm comprising clear 118 or 175 cm peaks. We demonstrate that the low-energy signals on Raman spectra of plasma-seeded grown graphene sheets originated from nanocurvature (c) of mono- (175 and 325-500 cm signals) (c ≈ 1 nm) and bilayer (118 cm peak) (c ≈ 2 nm) graphene with Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…19 Lee et al have shown that low-energy Raman signals of graphene structures (interpreted as RBM) are due to the radial mode (RM) formed by end curvatures of graphene of ∼2.2 nm diameter. 20 The RM model, where eigenvectors head for the center of the curvature of graphene structures, covers the RBM hypothesis of SWNTs. This indicates that the low-energy Raman signals are not unique to SWNTs and thus cannot be evidence for the tubular graphene structures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Lee et al have shown that low-energy Raman signals of graphene structures (interpreted as RBM) are due to the radial mode (RM) formed by end curvatures of graphene of ∼2.2 nm diameter. 20 The RM model, where eigenvectors head for the center of the curvature of graphene structures, covers the RBM hypothesis of SWNTs. This indicates that the low-energy Raman signals are not unique to SWNTs and thus cannot be evidence for the tubular graphene structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the low-energy Raman signals have been reported from graphene structures as well as thin nanographite comprising a few layers of graphene . Lee et al have shown that low-energy Raman signals of graphene structures (interpreted as RBM) are due to the radial mode (RM) formed by end curvatures of graphene of ∼2.2 nm diameter . The RM model, where eigenvectors head for the center of the curvature of graphene structures, covers the RBM hypothesis of SWNTs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the revelation of the edge of the sheet (Fig. 2b) is due to the nature of the 2D structures where the ends appear as curved (Lee et al, 2017).…”
Section: Structure Analysis Of H-bn Plateletsmentioning
confidence: 99%
“…Thus some researchers name the low-frequency Raman signals of the graphene structures as RBM-like without further explanation 11 , 15 or layer breathing modes of bilayer graphene 13 , 14 . Lee et al have shown that the low-frequency Raman signals of graphene structures (100–500 cm −1 ) are due to the radial mode (RM) formed by end nano-curvatures of mono- or bilayer graphene 16 . Indeed, the limit of the low-frequency Raman signals of SWNTs has been inconsistently reported to be ~ 200, ~ 250, ~ 300, ~ 350, and ~ 400 cm −1 , while some well-defined Raman spectra of SWNTs reveal many ripple-like peaks 1 5 , 17 27 distributed from ~ 200 cm −1 to ~ 1300 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the general understanding that it originated with synchronous radial vibration of the carbon atoms 2,3 in tubular graphene to be correlated with their diameters, affecting, in turn, their chirality 7 . The RBM mostly appears as a band comprising multiple peaks, and this band signal has been attributed to the presence of plural SWNTs with different diameters to be ~ 0.5-2 nm for 100-300 cm −1 from the equation, ω RBM (cm −1 ) = ~ 248/d where d is diameters of SWNTs 3-5 .The low-frequency Raman signals have also been observed from graphene (or nano-graphitic) structures [8][9][10][11][12][13][14][15][16] . This is unexpected because they are considered unique to SWNTs, i.e., tubular graphene.…”
mentioning
confidence: 99%